2016
DOI: 10.1038/emi.2016.99
|View full text |Cite
|
Sign up to set email alerts
|

Differential cell line susceptibility to the emerging Zika virus: implications for disease pathogenesis, non-vector-borne human transmission and animal reservoirs

Abstract: Zika virus (ZIKV) is unique among human-pathogenic flaviviruses by its association with congenital anomalies and trans-placental and sexual human-to-human transmission. Although the pathogenesis of ZIKV-associated neurological complications has been reported in recent studies, key questions on the pathogenesis of the other clinical manifestations, non-vector-borne transmission and potential animal reservoirs of ZIKV remain unanswered. We systematically characterized the differential cell line susceptibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 52 publications
(75 reference statements)
11
142
0
8
Order By: Relevance
“…ZIKV preferentially infects spermatogonia, primary spermatocytes, and Sertoli cells in the testis, resulting in cell death and destruction of the seminiferous tubules. In vitro studies have further shown that many cells lines derived from humans, primates, rodents, pigs, rabbit hamsters, chickens and mosquitoes, support productive ZIKV replication in vitro (Chan et al, 2016). These studies paved the way to use genetically tractable human cell types derived from iPSCs to investigate the underlying pathophysiology and molecular mechanisms of ZIKV infection.…”
Section: Modeling Of Zikv Exposurementioning
confidence: 99%
“…ZIKV preferentially infects spermatogonia, primary spermatocytes, and Sertoli cells in the testis, resulting in cell death and destruction of the seminiferous tubules. In vitro studies have further shown that many cells lines derived from humans, primates, rodents, pigs, rabbit hamsters, chickens and mosquitoes, support productive ZIKV replication in vitro (Chan et al, 2016). These studies paved the way to use genetically tractable human cell types derived from iPSCs to investigate the underlying pathophysiology and molecular mechanisms of ZIKV infection.…”
Section: Modeling Of Zikv Exposurementioning
confidence: 99%
“…Aunque la caracterización de la expresión de Axl en las células del sistema nervioso central puede explicar la entrada del ZIKV, es necesario adelantar más estudios para confirmar si dicho receptor determina el tropismo celular del virus en células neuronales cultivadas y en vivo, así como su capacidad para infectar fibroblastos de piel (43) y células epiteliales de cordón umbilical (44). Debe señalarse, además, que todavía no se han determinado completamente los receptores celulares del ZIKV.…”
Section: Discussionunclassified
“…Dicho neurotropismo diferencial durante el desarrollo se ha observado en estudios recientes en ratones, los cuales evidenciaron altos grados de infección por el ZIKV en el cerebro, la médula espinal (6,46) y las células epiteliales (44,46). Aunque no se sabe por qué algunas células epiteliales y neuronales son más propensas a la infección por el ZIKV que otras (por ejemplo, las neuronas progenitoras lo son más que las corticales maduras) (5,8,47), se podrían presentar diferentes mecanismos de entrada mediados por distintos tipos de receptores (por ejemplo, Axl o TAR), así como tasas de infección diferentes debido a cambios en el grado de expresión de factores del huésped requeridos para la entrada (por ejemplo, TLR3), la replicación o el ensamblaje del ZIKV (42).…”
Section: Discussionunclassified
“…Thus, they suggested that this provides evidence for the association between the virus and microcephaly. In contrast, Chan et al [37] found both viral replication and cytopathic effects in neuronal, placental, hepatic, colonic, retinal, pulmonary, and muscular cell lines. They found viral replication but not cytopathic effects in renal, testicular, and prostate cells.…”
Section: Pathogenesismentioning
confidence: 96%